Impak Pembangunan Tebingan Sungai Ke Atas Persekitaran Fizikal dan Manusia - Sakawi, Zaini (Journal of Techno-Social, 2009)
Development and environment are two phenomena which very synonym in recent development. Generally, development demands will bring positive or negative impact to the environment. Therefore, this paper work will discuss the study of the impact of Malacca River bank development at Bandar Hilir, Malacca to the environment, especially to human environment. The finding of this study shows that the impact of Malacca River bank construction and beautify can be classified into four main impacts. The impacts are restructuring of layout, tourists attraction, infrastructure development and environmental quality. The finding of this study also shows that river bank development and environmental changes give new shift to local society benefits to generate higher quality and dynamic life. In effort to attain the prosperous and equipoise in this river bank development, it is not involved only the administration, but also need the involvement of all parties such as the NGOs, mass media and society.